The Editorial preface - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2023)
TeMA Journal’s Special Issue Burn or sink - Planning and managing the land features a collection of eight original papers. These were written specifically for this issue following the call for papers launched in October 2022. The papers present ideas, theories, empirical insights, methodologies, experiences, and techniques about policy issues, best practices, and research findings on the Special Issue themes. TeMA Journal has already shown extensive interest in these aspects. Over its 16-year lifespan, the journal has explored broad themes that characterize today’s environmental crisis, with the aim of outlining new planning paths. For the first time, the journal’s editorial staff is proposing a Special Issue aimed at deepening the topic by soliciting articles focused on scientific aspects, the development of innovative practices, and the role of social behaviors.